The risk of genetic introgression from farmed escapees to wild cod populations - Skjaeraasen, J E; Meager, J J; Ferno, A (International Council for the Exploration of the Seas, 2009)
Global declines of commercially exploited fish have resulted in new aquaculture targets. One such species is the Atlantic cod (Gadus morhua) which is already being cultured in Norway, with farming also underway in Iceland, Scotland, and several other countries in the North Atlantic. It is necessary to assess the potential impact of this aquaculture on the already severely depleted wild stocks. As farming inevitably leads to genetic divergence from wild stocks, one potential adverse effect of fish farming is fitness depression in wild populations because of interbreeding between escaped farmed fish and wild fish. To assess this risk, we used a combined laboratory and field approach. We first examined morphological and physiological traits known to affect reproductive success of farmed and wild cod. We then examined the behaviour and reproductive success of farmed and wild cod breeding naturally in large mesocosm experiments. Finally, we used telemetry to investigate movements of wild and farmed cod on a natural field spawning ground. We found that hybridization between farmed and wild cod is likely, but that farmed females are the main vector for genetic introgression.